Financial Literacy in Halal Business Among Women Enterpreneurs - Miskiyyah, Millatul; Rodiah, Ita (Jurnal Masyarakat Maritim, 2024)
This study aims to explore the importance of financial literacy for women entrepreneurs in achieving maximum business performance, knowing the obstacles and success factors in entrepreneurship, and knowing women's empowerment policies in entrepreneurship. This research methodology uses descriptive qualitative research. The data collection techniques used are observation, interviews, and documentation studies. The results show that women entrepreneurs have great potential in entrepreneurial development and show a better quality of entrepreneurship for women entrepreneurs. This study explains that financial literacy is very important for women entrepreneurs to manage business finances well and help them face finance-related challenges and improve halal business performance.